Diagnostic Accuracy of Triphasic CT in the Characterization of Incidental Focal Liver Lesions - Farkhanda Jabeen, Natasha Khawaja Khail, Riffat Mushtaq, Ume Kalsoom (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the diagnostic accuracy of triphasic CT in the diagnosis of focal liver lesions as benign or malignant by using histopathology as the gold standard. Methods: This descriptive cross-sectional study was carried out at the diagnostic radiology department of the Pakistan Institute of Medical Sciences (P.I.M.S.) in Islamabad.110 individuals with localized liver lesions between the ages of 15 and 65 years and both genders were included. All of the study subjects were then undergoing triphasic CT scan of the liver. The CT findings were recorded as benign or malignant and correlated with histopathology findings. Data collection was done by using the self-structured proforma. Results: Patient’s mean age was 43.92 ± 12.87 years. Out of all, males were 68 (61.82%) and females were 42 (38.18%), with a female-to-male ratio of 1:1.6. Malignant lesions were 73 (66.36%) and 37 (33.54%) patients had benign lesions as per Triphasic CT diagnosis. Furthermore, in these 73 malignant cases, 67 cases were observed with malignant lesions and 6 cases had benign lesions on histopathology, while among the 37 CT cases of benign lesions, 8 cases had malignant lesions as per the histopathological diagnosis. Although triphasic CT showed 89.33% sensitivity and 82.86% specificity in the diagnosis of focal liver lesions by using histopathology as the gold standard. Conclusion: Triphasic CT was observed to be a non-invasive, accurate, and highly sensitive imaging technique in the diagnosis of focal liver lesions, whether (benign or malignant). Therefore, it can be used frequently to lower the number of pure diagnostic biopsies. Keywords: Malignant hepatic lesions, non-invasive, imaging modality, sensitivity